Target-Specific Exosome Isolation through Aptamer-Based Microfluidics - Zixuan Zhou; Yan Chen; Xiang Qian (Biosensors, 2022)
Exosomes (30–100 nm in diameter) are a group of cell-derived membrane vesicles, packaged as valuable cargo with lipid, proteins, and genetic materials from their parent cells. With the increasing interest in exosomes for diagnostic and therapeutic applications, the rapid isolation of pure exosome populations has become a hot topic. In this paper, we propose modified microchannels with aptamer in a microfluidics system for rapid and efficient isolation of exosomes by targeting exosome-carrying CD63 and PTK 7. The capture efficiency in surface-modified channels reaches around 107–108 particles/mL in 20 min, and purified exosomes with reliable size can be achieved.